Fabrication of Complex Polyelectrolyte Membrane of Chitosan-Pectin Crosslinked as Bioadsorbent - Silitonga, Friska Septiani (Talenta Publisher, 2019)
Biopolymers are polymers fabricated from natural polymers which are biodegradable, non-toxic and renewable. This research was aimed to synthesize and characterize biopolymer made from chitosan and pectin and was made to be a membrane cross-linked with glutaraldehyde and then characterized. The chitosan-pectin crosslinked glutaraldehyde polyelectrolite complex (PEC) and membrane can be used as a bioadsorbent for metal and cationic dyes. Firstly, PEC membrane chitosan-pectin crosslinked glutaraldehyde was synthesized by dissolving chitosan in acetic acid and pectin in distilled water and added with glutaraldehyde as a crosslinked agent, then heated at 70 °C. The amount of 1M NaOH solution was added for 12 hours and then cleaned with distilled water and dried at room temperature. Subsequently, the membrane was characterized with FTIR spectrophotometer, medium acidity test, and water uptake. The results of the characterization of PEC mebmbrane chitosan-pectin crosslinked glutaraldehyde with FTIR showed the interaction between –NH3+ of chitosan with –COO- group of pectin at a wavelength of 1604.77 cm-1. The medium acidity test showed that the PEC membrane chitosan-pectin crosslinked with glutaraldehyde was stable at pH 3-9 with water absorption of 266.67%, with the composition of chitosan-pectine membrane of 70:30 with 30% glutaraldehyde